Contrasting carbon and nitrogen responses to tillage at different soil depths: An observation after 40‐year of tillage management. Issue 4 (20th June 2021) - Parajuli, Binaya; Ye, Rongzhong; Luo, Min; Ducey, Thomas F.; Park, Dara; Smith, Matthew; Sigua, Gilbert
Abstract: Conservation tillage (CS) is a major component of sustainable soil management. The objective of the study was to investigate soil C and N pools and the associated microbial activities in sandy Ultisols after 40 yr of CS and conventional tillage (CT). Soil samples were collected from fields under continuous CS and CT for 40 yr (1979–2018) and subjected to a range of physio‐biogeochemical analyses. When compared with CT, CS increased total C, total N, and active C by 35, 45, and 44% at 0‐to‐5‐cm depth, respectively, but not at 5‐to‐15‐cm depth. In contrast, CT had 128 and 121% higher inorganic N and dissolved organic N at 5‐to‐15‐cm depth, which was not observed at 0‐to‐5‐cm depth. Respiratory CO2 production and organic N mineralization were found to be higher in CS soils than in CT soils at 0–5 cm, but both were higher in CT than CS at 5–15 cm. Concurrently with increased active C concentrations, potential activities of C‐cycling enzymes were higher in CS soils than CT soils at 0–5 cm, which was not observed at 5–15 cm. The increased labile C supply stimulated microbial activities in CS soils at 0–5 cm, but at 5–15 cm, the higher N availability increased microbial biomass N and organic N mineralization potentials in CT than CS soils. The contrasting CS and CT impacts on C and N at different soil depths likely reflected the decouple of C and N cycling in the tested soils. Core Ideas: Conservation tillage increased soil active C concentrations only at 0‐to‐5‐cm depth Increased active C stimulated microbial activities at 0–5 cm. Conventional tillage improved N availability in soils at 5–15 cm. Increased N availability at 5–15 cm induced higher microbial activities. Long‐term tillage managements resulted in contrasting C and N response at different soil depth.